Young Children's Emerging Understandings of the Measurement of mass. Issue 4 (December 2013) - McDonough, Andrea; Cheeseman, Jill; Ferguson, Sarah
THIS ARTICLE DESCRIBES INSIGHTS into young children's emerging understandings of the measurement of mass. Findings from a teaching experiment that delivered lessons offering rich learning experiences regarding concepts of mass to children of six to eight years of age (Years 1 and 2) suggest that, while the basic idea of direct measurement may look simple, the learning of mass measurement can involve complex mental accomplishments for young children. The lessons are described briefly to communicate the opportunities for exploration that they provided. Examples of children's actions and reasoning as they experimented, theorised, and challenged each other in their learning are also described. Complexities and accomplishments in these young children's emerging understandings are highlighted and discussed.